Mathematical Interaction and Communication Analysis in Jigsaw Type Cooperative Learning - 'Afifah, Nur (Jurnal Riset Ilmu Pendidikan, 2022)
The main problem of this study is that teacher seems dominating the class and it cause to the lack of student’s role in finding new concept of learning process. Consequently, the students develop their creativity to solve their problem by interacting one another and improve the communication in learning process. Referring to that concept, it is necessary to apply a learning system which increase students’ activity, and accommodate communication among them. Cooperative learning by jigsaw model is one alternative of mathematic learning to solve the case. This research is meant to deepen the students’ activities in cooperative learning, the students’ activities are focused on task student’s interaction to find the pattern of interaction. After learning process, will be depicted also the students’ mathematic communicative. The Subject of this research is the students in the second class of mathematic and natural field Student Mathematics FKIP UMSU, was applied the cooperative learning jigsaw type. The used instrument, is instrument of observation with reliability 0,91 and test instrument with reliability 0,86, and significant standard 0,05. The analysis result in qualitative part, was found general form of student’s interaction on task, namely interaction in discussion form to find the idea of task solution or negotiation to decide the group answer. While the student’s interaction based on academic ability are: (1) a high ability student interacted with a medium ability in order to help along with explanation; (2) a high ability student interacted with a low ability student in order to help without explanation; (3) a medium ability student interacted with a low ability student in order to help with explanation. The analysis result about the ability of students’ communication, was found the score mean of the students’ mathematic communication ability 68, 97. Many students have been able to communicate mathematic about 85%, and classically have been able to do it. Based on the result of this research, then the learning process in school has been properly in student center. The teacher has to be desirable to facilitate the students, in order to be able to interact each other to find, to express, and to using mathematic concept to deal with problem. The paradigm of the teacher to teach the students has to be done, because the students have ability that can be dug by them selves. Therefore, jigsaw cooperative learning is very good to apply as mathematic learning alternative at school